2020
DOI: 10.4236/jct.2020.111001
|View full text |Cite
|
Sign up to set email alerts
|

Using Prostatic Fluid Levels of Some Trace Elements and Their Combinations in Non-Invasive and Highly Accurate Screening for Prostate Cancer

Abstract: Objective: Prostate specific antigen (PSA) does not provide the high reliability and precision that is required for an accurate screening for prostate cancer (PCa). The aim of our study was to search for a simple, rapid, direct, preferably non-invasive, and highly accurate biomarker and procedure for the screening for PCa. Method: The levels of trace elements (TE) Br, Fe, Rb, Sr, and Zn were prospectively evaluated in expressed prostatic fluid (EPF). Also Zn/Br, Zn/Fe, Zn/Rb, Zn/Sr concentration ratios as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As was shown by us in our previous studies [39][40][41][42][43][44][45][46][47] results from the use of CRM IAEA H-4 as certified reference materials for the analysis of samples of EPF is acceptable. Good agreement of the Zn content, analyzed by the 109 Cd EDXRF method, with the certified data of reference materials indicates an acceptable accuracy for the results obtained in the study and presented in Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As was shown by us in our previous studies [39][40][41][42][43][44][45][46][47] results from the use of CRM IAEA H-4 as certified reference materials for the analysis of samples of EPF is acceptable. Good agreement of the Zn content, analyzed by the 109 Cd EDXRF method, with the certified data of reference materials indicates an acceptable accuracy for the results obtained in the study and presented in Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, the method and apparatus for micro analysis of Zn and some other TEs in the EPF samples using energy dispersive X-ray fluorescence (EDXRF) activated by radiation from the radionuclide source 109Cd (109Cd EDXRF) was developed by us [38]. It was found that data on changes of TE content and, particularly, Zn in EPF of patients with PCa are very important, because these significant changes increase our knowledge and recognition of PCa pathogenesis and may prove useful as PCa diagnostic markers [39][40][41][42][43][44][45][46][47]. It was concluded that the Zn in EPF, obtained by EDXRF, is a first candidate with the role of offering a new, simple, fast, reliable, and non-invasive diagnostic tool for PCa population screening [47].…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing EPF expressed from the prostates of eight apparently healthy men, aged 25 -55 years, it was found that Zn concentrations varied from 300 to 730 mg/L. After this finding several investigators suggested that the measurement of Zn levels in EPF may be useful as a marker of abnormal prostate secretory function [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Methodsmentioning
confidence: 99%